Violência denunciada: ocorrências de maus tratos contra crianças e adolescentes registradas em uma unidade policial. - Garbin, Clea Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Joaquim, Renata Colturato; de Paula, Adrielle Mendes; de Guimarães e Queiroz, Ana Paula Dossi (FapUNIFESP (SciELO), 2011)
This study aimed to investigate the profile of the occurrence of abuse against children and adolescents. We analyzed the data recorded in police reports from the Department of Women's Defense, Araçatuba-SP, in 2008, relating to assault, victim-offender relationship, sociodemographic characteristics of offenders and victims, and victims' demand for health services. Among the accusations, there was a higher prevalence of physical abuse, being the residence the place of higher incidence of aggression. In most cases, the aggressor was the mother of the child, being the subject of aggression not reported, in most cases. Thus, we can define the profile of violent incidents against children, contributing to the visualization, knowledge and to deal with the problem.
Reported violence: occurrences of maltreatment against children and adolescents registered in a police unit
Keywords: adolescent; child; child abuse; female; human; infant; male; police; preschool child; statistics; Adolescent; Child; Child Abuse; Child, Preschool; Female; Humans; Infant; Male; Police